(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
The present study explores detailed morphological and anatomical features of six variants of Canna indica L. Noticeable variations have been recorded in the morphology of six variants of C. indica especially on the basis of their different colours of leaves, flowers, staminodes and fruits. Root, stem and leaf anatomy of C. indica revealed little variation among the variants employed in the study. Phloem is 5-6 layered in the variant 2 (small red), 4-5 layered in the variant 4 (orange), and 3-4 layered in the remaining variants. The variant 4 (orange) can be distinguished from other five variants anatomically, by presence of 5-7 layers of schlerenchymatous tissue, and morphologically by its green pseudostem, ovate to obovate leaves, orange flowers, green bracts with maroon edges and orange-red staminodes. However, based on morphological and anatomical discrepancies the variants of Canna indica cannot be assigned to discrete taxonomic variety.